Invasive Mechanical Ventilation in Traumatic Brain Injured Patients with Acute Respiratory Failure - Racca, Fabrizio; Geraci, Cristina; Cremascoli, Luca; Ruvolo, Domenico; Piccolella, Fabio; Romenskaya, Tatsiana; Longhitano, Yaroslava; Martuscelli, Ermelinda; Saviano, Angela; Savioli, Gabriele; Zanza, Christian (Reviews on Recent Clinical Trials, 2023)
Patients with severe traumatic brain injury (TBI) need to be admitted to intensive care (ICU) because they require invasive mechanical ventilation (IMV) due to reduced consciousness resulting in loss of protective airway reflexes, reduced ability to cough and altered breathing control. In addition, these patients can be complicated by pneumonia and acute distress syndrome (ARDS). IMV allows these patients to be sedated, decreasing intracranial pressure and ensuring an adequate oxygen delivery and tight control of arterial carbon dioxide tension. However, IMV can also cause dangerous effects on the brain due to its interaction with intrathoracic and intracranial compartments. Moreover, when TBI is complicated by ARDS, the setting of mechanical ventilation can be very difficult as ventilator goals are often different and in conflict with each other. Consequently, close brain and respiratory monitoring is essential to reduce morbidity and mortality in mechanically ventilated patients with severe TBI and ARDS. Recently, recommendations for the setting of mechanical ventilation in patients with acute brain injury (ABI) were issued by the European Society of Intensive Care Medicine (ESICM). However, there is insufficient evidence regarding ventilation strategies for patients with ARDS associated with ABI. The purpose of this paper is to analyze in detail respiratory strategies and targets in patients with TBI associated with ARDS.
Keywords: positive end expiratory pressure